APLIKASI KOMPOS AMPAS SAGU (Metroxylon sagu) TERHADAP PERTUMBUHAN SEMAI JELUTUNG RAWA (Dyera lowii Hook.f) PADA MEDIUM GAMBUT - Azlina, Nur; Mardhiansyah, M.; Sribudiani, Evi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Revegetation is an effort to restore peatland after it is damaged. Dyera lowii is a type of forestry plant has a high potential to be developed because this tree is suitable for planting on peatland. To get good growth of Dyera lowii nutrients are needed, one of which is by providing compost. The solid waste of the sago industry that has accumulated will experience decomposition so that it becomes compost. The purpose of this research is to determine effect and the best dosage of sago dreg compost of Metroxylon sagu on the growth of Dyera lowii on peat media. The study used a Completely Randomized Design method consisting of 4 treatments and 4 replications so that 16 units of the experiment would be obtained. The treatments are : S1 = without Metroxylon sagu compost, S2 = 20% Metroxylon sagu compost + 80% peat soil, S3 = 50% Metroxylon sagu compost + 50% peat soil, S4 = 80% Metroxylon sagu compost + 20% peat soil. Data further analyzed using variance, with SPSS software version 20.0. If the results of variance have a significant effect, then further analysis is done using the DNMRT test at the 5% level. Application of sago dreg compost of Metroxylon sagu influences the growth of swamp Dyera lowii and the best dosage of the four treatments were S1 treatment (20% + 80% Metroxylon sagu compost) with 95% survival rate, 0.83 cm height increase, and plant dry weight 0.60 gr. Keywords: Metroxylon sagu compost, Dyera lowii  Hook.f, peat media